2020
DOI: 10.1101/2020.05.31.126581
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heat Shock Protein 27 Immune Complex Altered Signaling and Transport (ICAST): Novel Mechanisms of Attenuating Inflammation

Abstract: Blood levels of heat shock protein (HSP27) and natural IgG auto-antibodies to HSP27 (AAbs) are higher in healthy controls compared to cardiovascular disease patients. Vaccination of mice with recombinant HSP25 (rHSP25, murine ortholog of human rHSP27) increased AAb levels, attenuated atherogenesis and reduced plaque inflammation and cholesterol content. We sought to determine if the HSP27 immune complex (IC) altered MΦ inflammation signaling (Toll Like Receptor 4; TLR4), and scavenger receptors involved in cho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…What we also uncovered is a complex relationship between HSP27 and estrogens, as HSP27 acts as a repressor of estrogen-mediated transcription in vitro, yet its expression and extracellular release are also partially regulated by estrogens (e.g., there is an estrogen response element found in the HSP27 promoter) (Miller et al 2005;Rayner et al 2009). As well, we recently noted that natural IgG auto-antibodies to HSP27 (AAbs) are detectable in human blood (Chen et al 2020b) and demonstrated how HSP27 immune complexes (ICs) form, dock at the cell membrane where they engage with Toll-like receptor 4 (TLR4), and compete with LPS to reduce inflammatory signaling (Shi et al 2020). Interestingly, HSP27 activates the NF-κB pathway-but only modestly-resulting in the expression of both pro-and anti-inflammatory cytokines and proteins (Salari et al 2013).…”
Section: Covid-19 Hyper-inflammation and Sex-specific Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…What we also uncovered is a complex relationship between HSP27 and estrogens, as HSP27 acts as a repressor of estrogen-mediated transcription in vitro, yet its expression and extracellular release are also partially regulated by estrogens (e.g., there is an estrogen response element found in the HSP27 promoter) (Miller et al 2005;Rayner et al 2009). As well, we recently noted that natural IgG auto-antibodies to HSP27 (AAbs) are detectable in human blood (Chen et al 2020b) and demonstrated how HSP27 immune complexes (ICs) form, dock at the cell membrane where they engage with Toll-like receptor 4 (TLR4), and compete with LPS to reduce inflammatory signaling (Shi et al 2020). Interestingly, HSP27 activates the NF-κB pathway-but only modestly-resulting in the expression of both pro-and anti-inflammatory cytokines and proteins (Salari et al 2013).…”
Section: Covid-19 Hyper-inflammation and Sex-specific Featuresmentioning
confidence: 99%
“…Interestingly, HSP27 activates the NF-κB pathway-but only modestly-resulting in the expression of both pro-and anti-inflammatory cytokines and proteins (Salari et al 2013). Boosting HSP27 antibodies via vaccination reduces atherosclerosis and promotes the antiinflammatory effects of the HSP27 immune complex (Shi et al 2020). It is the combination of the protein and its antibody that produces the therapeutic benefit-a concept that we refer to as HSP27 Immune Complex Altered Signaling and Transport (or ICAST; transport refers to cellular internalization of HSP27).…”
Section: Covid-19 Hyper-inflammation and Sex-specific Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the in vitro role of exosomal HSP27 we will incorporate new information showing that anti-HSP27 IgG antibodies levels are more abundant in healthy subjects vs. CVD patients. To this end, we have generated and validated a polyclonal anti-HSP27 IgG antibody (PAb) that combines with HSP27 to form an immune complex (IC) that facilitates the biological effects of HSP27 (referred to as Immune Complex Altered Signaling and Transport (ICAST)) [18,26].…”
Section: Introductionmentioning
confidence: 99%
“…However, whether it plays a protective or destructive role in the in ammatory process is still controversial [7]. HSP27 and IL-17 can act through NF-κ B pathway [8][9][10]. But it is not clear whether there is a synergistic or antagonistic effect among them.…”
mentioning
confidence: 99%